Optimal quadrature formulas in Sobolev space for solving the generalized Abel integral equation - Daliyev Bakhtiyor; Tukxtasinov Dadakhon; Bozarov Bakhromjon; Sabirov Salim; Abdullayev Jamoliddin; Ruzimatova Makhfuza (E3S Web of Conferences, 2024)
In this article, a composite optimal quadrature formula is constructed for an approximate analytical solution of the generalized integral Abel equation in the Sobolev functional space. The optimal coefficients of this quadrature formula have been found. In addition, using the constructed composite optimal quadrature formula, numerical results of examples of the generalized Abel integral equation were obtained and compared with the exact solution.